2017
DOI: 10.1080/13685538.2017.1311857
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metabolic status on the association of serum vitamin D with hypogonadism and lower urinary tract symptoms/benign prostatic hyperplasia

Abstract: The clinical usefulness of vitamin D for treatment of hypogonadism or LUTS/BPH varies according to metabolic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
1
17
1
1
Order By: Relevance
“…Wang et al [64] found that Asian patients with MetS had a higher PSA level than non-MetS patients. However, according to others, the PSA level was similar in both groups [23,[30][31][32]34]. Our study suggested that no significant difference in PSA level between patients with and without MetS.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Wang et al [64] found that Asian patients with MetS had a higher PSA level than non-MetS patients. However, according to others, the PSA level was similar in both groups [23,[30][31][32]34]. Our study suggested that no significant difference in PSA level between patients with and without MetS.…”
Section: Discussionsupporting
confidence: 75%
“…In the final statistical analysis, there were 18 studies reported the PSA level [16,17,19,20,[22][23][24][25][26][27][28][30][31][32][33][34][35][36]. There was no statistical difference in PSA level between the presence of MetS and the absence of MetS (WMD ¼ 0.04; 95% Cl: À0.06 to 0.13; p ¼ .43; Figure 3).…”
Section: Prostate-specific Antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, clinical studies have been conducted to evaluate the effect of metabolic syndrome on the relationship between vitamin D level and lower urinary tract symptoms. Park et al evaluated the effect of metabolic syndrome on the relationship between vitamin D level and lower urinary tract symptoms and found that vitamin D level positively correlated with total testosterone level in patients without metabolic syndrome and negatively correlated with IPSS and prostate volume (21). In the study conducted by Caretta et al, the relation between vitamin D deficiency and lower urinary tract symptoms in type 2 diabetes mellitus (DM) patients was evaluated and it was observed that 25 OH vitamin D levels decreased progressively with increasing IPSS scores in type 2 DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is an essential, fat-soluble vitamin in human body, which is closely related to cell proliferation, differentiation, infection and immune system [ 7 ]. Uric acid is a marker of metabolic disorders and is associated with stroke, peripheral artery disease, and CHD[ 8 ].…”
Section: Introductionmentioning
confidence: 99%